2021
DOI: 10.2147/ijgm.s323136
|View full text |Cite
|
Sign up to set email alerts
|

The Coefficient of Variation of Red Blood Cell Distribution Width Combined with Cancer Antigen 125 Predicts Postoperative Overall Survival in Endometrial Cancer

Abstract: Purpose This study assessed the prognostic value of red blood cell distribution width (RDW) and cancer antigen 125 (CA125) in predicting the prognosis of endometrial cancer (EC) patients. Patients and Methods In this study, we included 525 patients with EC between January 2013 and January 2019. Demographic and clinical indicators were collected, and the receiver operating characteristics curve (ROC) and cutoff values were calculated between the early and advanced stages… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 23 publications
(36 reference statements)
1
4
0
Order By: Relevance
“…These results revealed that RDW may play a pivotal role in predicting the survival of patients with endometrial cancer, particularly those with advanced disease. This is consistent with previous findings in patients with other malignancies, including breast, lung, and gynecologic cancers [13][14][15][16][17].…”
Section: Discussionsupporting
confidence: 93%
“…These results revealed that RDW may play a pivotal role in predicting the survival of patients with endometrial cancer, particularly those with advanced disease. This is consistent with previous findings in patients with other malignancies, including breast, lung, and gynecologic cancers [13][14][15][16][17].…”
Section: Discussionsupporting
confidence: 93%
“…In clinical practice, CA125 has been routinely used to diagnose a variety of malignancies, especially epithelial ovarian cancer [ 28 ]. Quan et al [ 29 ] demonstrated that serum CA125 significantly correlated with clinicopathological risk factors, such as depth of myometrial invasion, LN status, and FIGO stage and that CA125 is a promising prognostic indicator for EC [ 30 , 31 ]. In our study, CA125 could be used as an independent predictor of PLNM in EC patients, which is consistent with the results of Lei et al [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Unsal et al, which included 423 patients with EEC, it was found that high CA-125 levels were associated with tumor spread and lymph node metastasis; however, after adjusting for age, in patients >50 years, the CA-125 cutoff value for predicting lymph node metastasis was found to be 16 IU/L 23 Zhong et al found that the red cell distribution width coefficient of variation and CA-125 levels were significantly increased in the advanced stage compared to within the early stage of endometrial cancer, showing that these patients had worse overall survival 24 . Yilmaz Baran et al showed that choosing a CA-125 level of 16 IU/L may be more beneficial for early stage endometrial cancer with negative prognostic factors.…”
Section: Discussionmentioning
confidence: 99%